2018
DOI: 10.1590/0102-311x00024918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on tooth loss among individuals under periodontal maintenance therapy: a systematic review and meta-analysis

Abstract: Dental mortality has been reported by longitudinal studies on periodontal maintenance therapy (PMT), but the independent effect of smoking on tooth loss (TL), adjusted for important confounding variables, has been poorly evaluated. This systematic review aimed to assess and analyze the isolated effect of smoking TL among individuals undergoing PMT. Electronic, manual, grey literature, and recent articles (from April 2018) were searched, with no restriction regarding language; respective dates of publication we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Thus, in general, the majority of evidence indicates that smokers are at increased risk for the presence of unresponsive periodontal pockets and further periodontal breakdown during PMT. In several studies, two‐ to seven‐fold higher risk for RP were reported in CS when compared with FS and NS …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, in general, the majority of evidence indicates that smokers are at increased risk for the presence of unresponsive periodontal pockets and further periodontal breakdown during PMT. In several studies, two‐ to seven‐fold higher risk for RP were reported in CS when compared with FS and NS …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with a systematic review from a Brazilian research group that assessed smoking habits influencing tooth loss during long‐term PMT. Authors demonstrated that smoking was markedly associated with tooth loss . Paradoxically, the signs and symptoms of gingival inflammation are less pronounced in CS than in NS .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations